2014
DOI: 10.14710/jitaa.39.4.217-223
|View full text |Cite
|
Sign up to set email alerts
|

FEEDING EFFECT OF INULIN DERIVED FROM Dahlia variabilis TUBER ON INTESTINAL MICROBES IN STARTER PERIOD OF CROSSBRED NATIVE CHICKENS

Abstract: Penelitian ini bertujuan untuk mengkaji efek pemberian inulin dari umbi Dahlia variabilis, baik dalam bentuk tepung maupun ekstrak, terhadap keberadaan mikroba usus halus pada ayam kampung persilangan periode starter. Materi penelitian adalah 280 ekor ayam kampung persilangan unsex, dan tepung maupun ekstrak umbi dahlia sebagai sumber inulin yang mulai diberikan pada umur 22 hari. Penelitian menggunakan rancangan acak lengkap dengan 7 perlakuan dan 4 ulangan (masing-masing 10 ekor ayam). Perlakuan terdiri dari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
4
8
0
4
Order By: Relevance
“…The decrease in pathogenic bacteria population was an indication of the improved health status of the gastrointestinal tract that bring about the increase in crossbred kampong chicken body resistance. This evidence supported by previous results (Krismiyanto et al, 2014) that E.coli count reduced with feeding inulin in starter period of crossbred native chicken. The improvement of health status of gastrointestinal tract implicated to the improved antioxidant activity in body tissue.…”
Section: Resultssupporting
confidence: 92%
“…The decrease in pathogenic bacteria population was an indication of the improved health status of the gastrointestinal tract that bring about the increase in crossbred kampong chicken body resistance. This evidence supported by previous results (Krismiyanto et al, 2014) that E.coli count reduced with feeding inulin in starter period of crossbred native chicken. The improvement of health status of gastrointestinal tract implicated to the improved antioxidant activity in body tissue.…”
Section: Resultssupporting
confidence: 92%
“…This result is in agreement with the report of Krismiyanto et al (2014) that the increased lactic acid bacteria (LAB) population was due to the feeding effect of inulin derived from dahlia tuber which can intensely fermented by endogenous beneficial bacteria. Thus, the drecreased fat meat content and cholesterol concentration found in the present study can be associated with the increase in bile salt hydrolase (BSH) enzyme produced by the enhanced growth of LAB (Fajrih et al, 2014).…”
Section: Level Of Dahlia Tuber Powdersupporting
confidence: 93%
“…Peran et al (2007) and Rajput et al (2013) have also reported that probiotics can prevent oxidative damage to the small intestine caused by pathogenic bacteria by releasing GSH-Px enzyme as an antioxidant. We speculate that the increased antioxidant activity in body tissues of broilers by E. faecium supplementation might be associated with the improvement of the health of the gastrointestinal tract, which has been proposed by a previous study (Krismiyanto, Suthama, & Wahyuni, 2014).…”
Section: Antioxidant Activitiessupporting
confidence: 62%